Synthesis and characterization of water-soluble polyvinyl alcohol/pomegranate peel powder films - Wong, Sim Yoong; Wan Norfazilah, Wan Ismail (Biointerface Research, 2020)
Biodegradable plastics had gained much attention among the researchers due to the arising of sustainability and environmental issues caused by petrochemical-based plastics. In this study, PVA films incorporated with pomegranate peel powder (PPP) were synthesized by using solution casting method. The effect of PPP on the surface morphology, physical properties, barrier properties and antibacterial activity of PVA based films were studied through FE-SEM, water solubility test, water contact angle test and Kirby-Bauer test. The incorporation of PPP had significantly enhanced the water solubility and surface energy of PVA-PPP films with the increasing of PPP content that caused reduction in water contact angle of the films. However, the films do not show a significant effect on the antibacterial efficacy against E.coli. In conclusion, PVA-PPP films have great potential to be used as green packaging materials for cosmetics products provided that further study on antibacterial efficacy against gram positive bacteria should be conducted.